BaTi2O5 modified ceramics, their preparation methods and applications

CN122940446APending Publication Date: 2026-10-20GUANGZHOU POWER SUPPLY BUREAU GUANGDONG POWER GRID CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611027783.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-10
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,该体系在应用过程中仍存在以下技术瓶颈:一方面,传统配方体系的烧结温度较高,导致制备能耗大,且高温下玻璃相含量偏高,易在晶界处形成非晶态薄弱层,降低材料的体积电阻率和击穿强度,长期电场作用下易引发局部放电和绝缘老化;另一方面,受制于晶粒尺寸分布不均和晶界结合强度不足,材料的抗弯强度和断裂韧性偏低,在强风、覆冰、地震等极端机械载荷下易发生脆性断裂,严重威胁输电线路的运行安全

Benefits of technology

[0028]本申请的制备方法通过将BaTi2O5纳米线引入绝缘子陶瓷基体原料中,结合压制成型过程中的压力诱导使高长径比纳米线发生择优取向旋转,并配合分段烧结工艺,从而在取向方向上Ba元素与陶瓷基体原料内的含有的Si、Al等元素的成分发生界面反应生成液相,充分润湿氧化铝、氧化硅颗粒并通过溶解-沉淀机制持续填充坯体内部连通气孔,产生了显著提升陶瓷材料致密度、降低气孔率的效果;通过钛元素少量固溶进入氧化铝晶格引发晶格畸变,同时钡钛相偏析于晶界起到钉扎作用,抑制氧化铝晶粒异常长大、避免气孔被包裹滞留于晶粒内部,加速气孔排出与晶界融合,协同产生了构建晶粒规整、晶界致密、少缺陷微观结构,消除局部电场集中,显著改善陶瓷脆性的效果。基于上述制备步骤的相互协同,获得了兼具高致密度、高电气绝缘强度和高抗弯强度的BaTi2O5改性陶瓷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This application relates to the field of insulator technology, and particularly to BaTi2O5 modified ceramics, their preparation methods, and applications. The preparation method includes: mixing insulator ceramic matrix raw materials, BaTi2O5 nanowires, binders, and sintering aids to obtain a mixed raw material; pressing the mixed raw material into a green blank, and then performing segmented sintering: heating from 20℃-40℃ to 550℃-650℃ at a rate of 4.5℃ / min-5℃ / min, holding at that temperature for 25min-35min; heating from 550℃-650℃ to 1050℃-1150℃ at a rate of 2.5℃ / min-3.5℃ / min, holding at that temperature for 25min-35min; and heating from 1050℃-1150℃ to 1200℃-1300℃ at a rate of 1.5℃ / min-2.5℃ / min, holding at that temperature for 2h-3h. The BaTi2O5 modified ceramic of this application exhibits excellent electrical insulation properties and mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of insulator technology, and in particular to BaTi2O5 modified ceramics, their preparation methods, and applications. Background Technology

[0002] High-voltage ceramic insulators are indispensable key insulation components in high-voltage transmission lines, and their performance directly affects the safe and stable operation of the power system. With the continuous increase in transmission voltage levels and the increasing complexity of operating environments (such as heavy pollution, high humidity, and strong ultraviolet radiation), more stringent requirements are being placed on the electrical insulation performance and mechanical load-bearing capacity of ceramic insulators.

[0003] Currently, the preparation of high-voltage insulator ceramics typically uses high-alumina raw materials (such as industrial alumina) and siliceous raw materials (such as quartz) as a base, supplemented with sintering aids such as clay and feldspar, and is sintered at high temperatures to obtain ceramic materials with corundum (α-Al2O3) and mullite (3Al2O3·2SiO2) as the main crystalline phases. However, this system still faces the following technical bottlenecks in its application: On the one hand, the sintering temperature of traditional formulation systems is relatively high, resulting in high energy consumption in preparation, and the glass phase content is relatively high at high temperatures, which easily forms an amorphous weak layer at the grain boundaries, reducing the volume resistivity and breakdown strength of the material, and easily causing partial discharge and insulation aging under long-term electric field action; on the other hand, due to uneven grain size distribution and insufficient grain boundary bonding strength, the bending strength and fracture toughness of the material are relatively low, and it is prone to brittle fracture under extreme mechanical loads such as strong winds, icing, and earthquakes, seriously threatening the operational safety of transmission lines. Summary of the Invention

[0004] To address the problems existing in the prior art, one or more embodiments of this application provide BaTi2O5 modified ceramics, their preparation methods, and applications. These BaTi2O5 modified ceramics possess excellent electrical insulation properties and mechanical strength, which can improve the service performance of insulators and ensure the stability of power grid operation.

[0005] One or more embodiments of this application provide a method for preparing BaTi2O5 modified ceramics, comprising the following steps:

[0006] A mixed raw material is prepared by mixing insulator ceramic matrix raw material, BaTi2O5 nanowires, binder and sintering aid;

[0007] After the mixed raw materials are pressed into green blanks, they are sintered in sections.

[0008] The segmented sintering process includes:

[0009] The temperature was increased from 20℃-40℃ to 550℃-650℃ at a rate of 4.5℃ / min-5℃ / min, and then held for 25min-35min.

[0010] The temperature was increased from 550℃-650℃ to 1050℃-1150℃ at a rate of 2.5℃ / min-3.5℃ / min, and then held for 25min-35min.

[0011] The temperature was increased from 1050℃-1150℃ to 1200℃-1300℃ at a rate of 1.5℃ / min-2.5℃ / min, and then held for 2-3 hours.

[0012] In some embodiments, the length of the BaTi2O5 nanowires is 4 μm-6 μm; and / or,

[0013] The diameter of the BaTi2O5 nanowires is 100nm-200nm.

[0014] In some embodiments, the aspect ratio of the BaTi2O5 nanowires is 30:1-40:1.

[0015] In some embodiments, the insulator ceramic matrix raw material comprises the following mass percentages of oxides: SiO2 58.8%-63.7%, Al2O3 35.3%-40.2%, and unavoidable impurities ≤1%.

[0016] In some embodiments, the adhesive comprises at least one selected from polyvinyl alcohol, polyvinyl butyral, polyethylene glycol, methylcellulose, carboxymethylcellulose, paraffin wax, ammonium polyacrylate, and ethylene-vinyl acetate copolymer; and / or,

[0017] The sintering aid includes one or more of the following: talc, potassium carbonate, magnesium oxide, calcium oxide, calcium carbonate, dolomite, feldspar, boric acid, zinc oxide, yttrium oxide, barium carbonate, and titanium dioxide.

[0018] In some embodiments, the mass of the BaTi2O5 nanowires accounts for 1%-7% of the total mass of the insulator ceramic matrix raw material; and / or,

[0019] The binder accounts for 0.5%-0.8% of the total mass of the insulator ceramic matrix raw material; and / or,

[0020] The mass of the sintering aid accounts for 3%-5% of the total mass of the insulator ceramic matrix raw materials.

[0021] In some embodiments, the step of pressing the mixed raw material into a blank includes: subjecting the mixed raw material to compression molding at 10MPa-15MPa.

[0022] One or more embodiments of this application also provide BaTi2O5 modified ceramics, which are prepared using the preparation method described above.

[0023] In some embodiments, the BaTi2O5 modified ceramic has one or more of the following characteristics:

[0024] (1) Moisture absorption rate ≤ 0.5%;

[0025] (2) Breakdown strength ≥ 13kV / mm;

[0026] (3) Bending strength ≥ 100 MPa.

[0027] One or more embodiments of this application also provide the application of the BaTi2O5 modified ceramics described above in the preparation of high-voltage insulators.

[0028] The preparation method of this application introduces BaTi2O5 nanowires into the ceramic matrix raw material of insulators. Combined with pressure induction during the pressing process, the high aspect ratio nanowires undergo preferred orientation rotation. This, along with a segmented sintering process, allows Ba elements to react with Si, Al, and other elements in the ceramic matrix raw material along the orientation direction, generating a liquid phase. This liquid phase fully wets alumina and silica particles and continuously fills the interconnected pores inside the green body through a dissolution-precipitation mechanism, significantly improving the density and reducing the porosity of the ceramic material. A small amount of titanium dissolved into the alumina lattice induces lattice distortion, while the barium-titanium phase segregates at the grain boundaries, acting as a pinning agent. This inhibits abnormal alumina grain growth, prevents pores from being trapped inside the grains, and accelerates pore expulsion and grain boundary fusion. This synergistic process results in a well-structured, dense, and defect-free microstructure, eliminating localized electric field concentration and significantly improving the brittleness of the ceramic. Based on the synergistic effects of the above preparation steps, a BaTi2O5 modified ceramic with high density, high electrical insulation strength, and high flexural strength is obtained.

[0029] The BaTi2O5 modified ceramics prepared by the method of this application have excellent properties such as high volume resistivity, high breakdown strength, high flexural strength, good fracture toughness, and uniform and dense microstructure.

[0030] The BaTi2O5 modified ceramic of this application, when used in high-voltage insulators, effectively suppresses leakage current and partial discharge due to its high density and regular grain boundary structure. Simultaneously, grain refinement and grain boundary pinning significantly enhance the ceramic's resistance to mechanical loads. Therefore, it exhibits excellent electrical insulation properties and mechanical strength, effectively improving the insulator's service reliability, extending its service life, and ensuring the stability of the power grid operation. Furthermore, this preparation method is fully compatible with the large-scale production lines of traditional ceramic insulators, requiring no additional equipment and demonstrating excellent prospects for industrial production. Attached Figure Description

[0031] To more clearly illustrate the technical solutions in the specific embodiments of this application or the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0032] Figure 1 This is a process flow diagram for preparing BaTi2O5 modified ceramics according to one embodiment of this application.

[0033] Figure 2 XRD pattern of BaTi2O5 nanowires used in embodiments of this application.

[0034] Figure 3 SEM images of BaTi2O5 nanowires used in the embodiments of this application, with a scale bar of 2 μm.

[0035] Figure 4 This is a comparison of the XRD patterns of BaTi2O5 modified ceramics in Comparative Example 1 and Examples 1-3 of this application.

[0036] Figure 5 SEM images of the cross sections of BaTi2O5 modified ceramics of Comparative Example 1 and Examples 1-4 of this application; (a) Example 1, (b) Example 2, (c) Example 3, (d) Example 4, (e) Comparative Example 1, (f) Comparative Example 2, (g) Comparative Example 3.

[0037] Figure 6 This is a comparison chart of the densities of BaTi2O5 modified ceramics in Comparative Example 1 and Examples 1-4 of this application.

[0038] Figure 7 This is a comparison chart of the moisture absorption rates of BaTi2O5 modified ceramics in Comparative Example 1 and Examples 1-4 of this application. Detailed Implementation

[0039] The present application is further described below with reference to embodiments and examples. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the application. Furthermore, it should be understood that after reading the teachings of this application, those skilled in the art can make various alterations or modifications to this application, and these equivalent forms also fall within the protection scope of the appended claims.

[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application.

[0041] The term "and / or" as used herein includes any one of two or more related listed items, as well as any and all combinations of the related listed items. These arbitrary and all combinations encompass any two related listed items, any more related listed items, or a combination of all related listed items. It should be noted that when at least three items are connected using at least two conjunctions selected from "and / or," it should be understood that, in this application, the technical solution undoubtedly includes solutions connected using "logical AND," and also undoubtedly includes solutions connected using "logical OR." For example, "A and / or B" includes three parallel solutions: A, B, and A+B. For example, the technical solution of "A, AND / OR, B, AND / OR, C, AND / OR, D" includes any one of A, B, C, and D (that is, a technical solution that is connected by "logical OR"), as well as any and all combinations of A, B, C, and D, that is, combinations of any two or three of A, B, C, and D, and also combinations of all four of A, B, C, and D (that is, a technical solution that is connected by "logical AND").

[0042] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.

[0043] In this application, numerical intervals (i.e., numerical ranges) are involved. Unless otherwise specified, optional numerical distributions within the aforementioned numerical intervals are considered continuous and include the two endpoints (i.e., the minimum and maximum values) of the numerical range, as well as every value between these two endpoints. Unless otherwise specified, when a numerical interval points to integers within that interval, it includes the two endpoint integers of the numerical range, as well as every integer between the two endpoints. Furthermore, when multiple ranges are provided to describe features or characteristics, these ranges may be merged. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all subranges to which they are included.

[0044] In this application, weight can be a well-known unit of mass in the field of insulator materials, such as μg, mg, g, or kg.

[0045] In recent years, titanate functional ceramics have attracted attention due to their unique ferroelectric, piezoelectric, and high dielectric properties. Among them, BaTi2O5, as a low-melting-point barium titanate compound, possesses a high dielectric constant and good temperature stability, and its coefficient of thermal expansion shows some matching with that of alumina-based ceramics. However, currently, BaTi2O5 is mainly used in electronic ceramic capacitors and microwave devices, and its application in high-voltage insulator ceramics has not been systematically studied.

[0046] See Figure 1 One or more embodiments of this application provide a method for preparing BaTi2O5 modified ceramics, comprising the following steps:

[0047] S1. Mix the insulator ceramic matrix raw material, BaTi2O5 nanowires, binder and sintering aid to obtain a mixed raw material;

[0048] S2. After pressing the mixed raw materials into green blanks, they are sintered in sections.

[0049] The segmented sintering process includes:

[0050] The temperature was increased from 20℃-40℃ to 550℃-650℃ at a rate of 4.5℃ / min-5℃ / min, and then held for 25min-35min.

[0051] The temperature was increased from 550℃-650℃ to 1050℃-1150℃ at a rate of 2.5℃ / min-3.5℃ / min, and then held for 25min-35min.

[0052] The temperature was increased from 1050℃-1150℃ to 1200℃-1300℃ at a rate of 1.5℃ / min-2.5℃ / min, and then held for 2-3 hours.

[0053] In some embodiments, the length of the BaTi2O5 nanowire is 4μm-6μm. For example, the length of the BaTi2O5 nanowire can be, but is not limited to, 4μm, 4.5μm, 5μm, 5.5μm, and 6μm.

[0054] In some embodiments, the diameter of the BaTi2O5 nanowire is 100nm-200nm. For example, the diameter of the BaTi2O5 nanowire can be, but is not limited to, 100nm, 150nm, 175nm, or 200nm.

[0055] In some embodiments, the aspect ratio of BaTi2O5 nanowires is 30:1-40:1. Exemplarily, the aspect ratio of BaTi2O5 nanowires can be, but is not limited to, 30:1, 35:1, 37:1, 38:1, and 40:1. Within the above aspect ratio range, BaTi2O5 nanowires can be preferentially oriented under pressure. The barium and titanium elements, through fluxing and lattice distortion grain boundary pinning effects, densify and refine the ceramic to obtain high-performance ceramics.

[0056] In some embodiments, the insulator ceramic matrix raw material comprises the following mass percentages of oxides: SiO2 58.8%-63.7%, Al2O3 35.3%-40.2%, and unavoidable impurities ≤1%.

[0057] In some embodiments, the ceramic matrix material for insulators includes quartz and alumina.

[0058] In some embodiments, the insulator ceramic material comprises 60-65 parts of quartz and 35-40 parts of alumina by weight. Exemplarily, the weight of quartz may be, but is not limited to, 60, 61, 62, 63, 64, or 65 parts; and the weight of alumina may be, but is not limited to, 35, 36, 37, 38, or 40 parts.

[0059] In some embodiments, alumina is in the form of powder with a particle size D50 of 200 nm to 400 nm. Exemplarily, the particle size D50 of the alumina powder can be, but is not limited to, 200 nm, 250 nm, 300 nm, 350 nm, or 400 nm. Using ultrafine alumina powder with the above-mentioned particle size is beneficial for further improving sintering activity, filling grain gaps, and further improving the crystallinity and density of ceramic insulating components.

[0060] In some embodiments, the binder includes at least one selected from polyvinyl alcohol, polyvinyl butyral, polyethylene glycol, methylcellulose, carboxymethylcellulose, paraffin wax, ammonium polyacrylate, and ethylene-vinyl acetate copolymer. Preferably, the binder includes one or more selected from polyvinyl alcohol and polyvinyl butyral. The polymers exemplified above have a molecular weight in the range of 10,000-200,000 and have the function of increasing adhesion and enhancing the strength of the preform.

[0061] In some embodiments, the sintering aid includes one or more of talc, potassium carbonate, magnesium oxide, calcium oxide, calcium carbonate, dolomite, feldspar, boric acid, zinc oxide, yttrium oxide, barium carbonate, and titanium dioxide. Preferably, the sintering aid is potassium carbonate, where the K and Ba elements, as well as elements such as Si and Al, undergo an interfacial reaction to generate a liquid phase. This liquid phase fully wets the alumina and silica particles and continuously fills the interconnected pores inside the green body through a dissolution-precipitation mechanism, thereby better improving the density of the ceramic material and reducing its porosity.

[0062] In some embodiments, the mass of BaTi2O5 nanowires accounts for 1%-7% of the total mass of the insulator ceramic matrix raw material. For example, the mass of BaTi2O5 nanowires accounts for 1%, 3%, 5%, or 7% of the total mass of the insulator ceramic matrix raw material. Within the above-mentioned addition range, the BaTi2O5 nanowires can form sufficient directional orientation while avoiding agglomeration caused by excessive nanowires, thus achieving synergistic optimization of electrical insulation performance and mechanical strength.

[0063] In some embodiments, the mass of the binder accounts for 0.5%-0.8% of the total mass of the insulator ceramic matrix raw material. Exemplarily, the mass of the binder accounts for 0.5%, 0.6%, 0.7%, or 0.8% of the total mass of the insulator ceramic matrix raw material.

[0064] In some embodiments, the sintering aid accounts for 3%-5% of the total mass of the insulator ceramic matrix raw materials. Exemplarily, the sintering aid accounts for 3%, 3.5%, 4%, 4.5%, or 5% of the total mass of the insulator ceramic matrix raw materials.

[0065] In some embodiments, the step of mixing the insulator ceramic matrix material, BaTi2O5 nanowires, binder, and sintering aid includes:

[0066] The insulator ceramic matrix raw material and BaTi2O5 nanowires are mixed and ground. After grinding, binder and sintering aid are added and mixed.

[0067] In some embodiments, the grinding method includes ball milling.

[0068] In some embodiments, the ball milling conditions include: a ball milling speed of 100 rpm to 200 rpm and a ball milling time of 6 h to 8 h. Exemplarily, the ball milling speed can be, but is not limited to, 100 rpm, 120 rpm, 130 rpm, 140 rpm, 150 rpm, 160 rpm, 170 rpm, 180 rpm, 190 rpm, or 200 rpm; and the ball milling time can be, but is not limited to, 6 h, 6.5 h, 7 h, 7.5 h, or 8 h.

[0069] In some embodiments, the ball milling media are zirconia balls, and further selected are zirconia balls with diameters of 4.5mm-5.5mm, 7.5mm-8.5mm and 9.5mm-10.5mm, respectively, and the three are mixed in a mass ratio of 1:1:1.

[0070] In some embodiments, the step of pressing the mixed raw materials into a preform includes: subjecting the mixed raw materials to compression molding at a pressure of 10 MPa-15 MPa. Exemplarily, the compression molding pressure can be, but is not limited to, 10 MPa, 11 MPa, 12 MPa, 13 MPa, 14 MPa, or 15 MPa.

[0071] In some embodiments, the pressure applied during the compression molding process is a directional pressure.

[0072] One or more embodiments of this application also provide BaTi2O5 modified ceramics, which are prepared using the preparation method described above.

[0073] In some embodiments, BaTi2O5 modified ceramics have one or more of the following characteristics:

[0074] (1) Moisture absorption rate ≤ 0.5%;

[0075] (2) Breakdown strength ≥ 13kV / mm;

[0076] (3) Bending strength ≥ 100 MPa.

[0077] In some embodiments, the moisture absorption rate of the BaTi2O5 modified ceramic is ≤0.5%; further, the moisture absorption rate is 0.5%~0.3%. Exemplarily, the moisture absorption rate can be, but is not limited to, 0.5%, 0.4%, or 0.3%.

[0078] In some embodiments, the breakdown strength of the BaTi2O5 modified ceramic is ≥13kV / mm; further, the breakdown strength of the BaTi2O5 modified ceramic is 13kV / mm to 15kV / mm. Exemplarily, the breakdown strength can be, but is not limited to, 13kV / mm, 13.5kV / mm, 14kV / mm, 14.5kV / mm, and 15kV / mm.

[0079] In some embodiments, the flexural strength of the BaTi2O5 modified ceramic is ≥100MPa; further, the flexural strength of the BaTi2O5 modified ceramic is 100MPa~150MPa. Exemplarily, the flexural strength can be, but is not limited to, 100MPa, 110MPa, 120MPa, 130MPa, 140MPa, and 150MPa.

[0080] One or more embodiments of this application also provide the application of the BaTi2O5 modified ceramics described above in the preparation of high-voltage insulators.

[0081] The following are some specific examples.

[0082] For experimental parameters not specified in the following specific embodiments, please refer to the guidelines provided in this application, or consult experimental manuals or other known experimental methods in the field, or refer to the manufacturer's recommended experimental conditions. Raw materials and reagents not mentioned can be obtained commercially, or can be prepared by those skilled in the art using known methods.

[0083] The BaTi2O5 nanowires used in the following examples: XRD and SEM test results are available in [reference needed]. Figure 2 and Figure 3 .like Figure 2 As shown, the diffraction peaks of the BaTi2O5 nanowires correspond perfectly to the BaTi2O5 standard card, with no impurity phase peaks, indicating that the BaTi2O5 nanowires used have extremely high crystal phase purity.

[0084] like Figure 3 As shown, the BaTi2O5 nanowires exhibit a distinct one-dimensional linear morphology with regular shape and uniform size distribution. Through measurement and calculation, the length of the BaTi2O5 nanowires is 5 μm, the diameter is 150 nm, and the length-to-diameter ratio is 33:1.

[0085] Example 1

[0086] This embodiment provides a method for preparing the BaTi2O5 modified ceramic of this application, including the following steps:

[0087] (1) Weigh the following substances in parts by mass: 62 parts quartz, 38 parts alumina powder (particle size D50 is 300 nm), 10 parts BaTi2O5 nanowires, 0.7 parts polyvinyl alcohol (binder) with a degree of polymerization of 1000, and 4 parts potassium carbonate (sintering aid).

[0088] (2) Mix quartz, alumina powder and BaTi2O5 nanowires and ball mill them at 150 rpm for 7 hours. The grinding balls are zirconia balls of 5 mm, 8 mm and 10 mm in a mass ratio of 1:1:1. Then add binder and sintering aid and mix.

[0089] (3) Apply a directional pressure of 12 MPa to the mixture and press it to form a blank.

[0090] (4) The green blank is sintered in stages. The staged sintering procedure is as follows: 5 The temperature was increased from room temperature (25°C) to 600°C at a rate of ℃ / min, and held for 30 minutes. min; with 3 The temperature was increased from 600℃ to 1100℃ at a rate of ℃ / min and held for 30 minutes. min; with 2 The temperature was increased from 1100℃ to 1300℃ at a rate of ℃ / min and held for 2.5 seconds. h; then it is cooled in the furnace.

[0091] Example 2

[0092] This embodiment provides a method for preparing the BaTi2O5 modified ceramic of this application, which is basically the same as the preparation steps in Example 1, except that: Step (1) weigh the following materials in parts by mass: 60 parts of quartz, 40 parts of alumina powder (particle size D50 is 300 nm), 1 part of BaTi2O5 nanowires, 0.5 parts of polyvinyl alcohol (binder) with a degree of polymerization of 1000, and 4 parts of potassium carbonate (sintering aid); Step (3) apply a directional pressure of 10 MPa to the mixture for molding; Step (4) the segmented heating sintering procedure is as follows: at 5 The temperature was increased from room temperature (25°C) to 600°C at a rate of ℃ / min, and held for 30 minutes. min; with 3 The temperature was increased from 600℃ to 1100℃ at a rate of ℃ / min and held for 30 minutes. min; with 2 The temperature was increased from 1100℃ to 1300℃ at a rate of ℃ / min and held for 2 hours; then cooled in the furnace.

[0093] Example 3

[0094] This embodiment provides a method for preparing the BaTi2O5 modified ceramic of this application, which is basically the same as the preparation steps in Example 1, except that: Step (1) weigh the following materials in parts by mass: 65 parts of quartz, 35 parts of alumina powder (particle size D50 is 300 nm), 3 parts of BaTi2O5 nanowires, 0.8 parts of polyvinyl alcohol (binder) with a degree of polymerization of 1000, and 4 parts of potassium carbonate (sintering aid); Step (3) apply a directional pressure of 15 MPa to the mixture for molding; Step (4) the segmented heating sintering procedure is as follows: at 5 The temperature was increased from room temperature (25°C) to 600°C at a rate of ℃ / min, and held for 30 minutes. min; with 3 The temperature was increased from 600℃ to 1100℃ at a rate of ℃ / min and held for 30 minutes. min; with 2 The temperature was increased from 1100℃ to 1300℃ at a rate of ℃ / min and held for 3 hours; then cooled in the furnace.

[0095] Example 4

[0096] This embodiment provides a method for preparing the BaTi2O5 modified ceramic of this application, which is basically the same as the preparation steps in Example 1, except that: Step (1) weigh the following materials in parts by mass: 65 parts of quartz, 35 parts of alumina powder (particle size D50 is 300 nm), 7 parts of BaTi2O5 nanowires, 0.8 parts of polyvinyl alcohol (binder) with a degree of polymerization of 1000, and 4 parts of potassium carbonate (sintering aid); Step (3) apply a directional pressure of 15 MPa to the mixture for molding; Step (4) the segmented heating sintering procedure is as follows: at 5 The temperature was increased from room temperature (25°C) to 600°C at a rate of ℃ / min, and held for 30 minutes. min; with 3 The temperature was increased from 600℃ to 1100℃ at a rate of ℃ / min and held for 30 minutes. min; with 2 The temperature was increased from 1100℃ to 1300℃ at a rate of ℃ / min and held for 3 hours; then cooled in the furnace.

[0097] Comparative Example 1

[0098] This comparative example provides another method for preparing insulator ceramics, which is basically the same as the preparation steps in Example 1, except that BaTi2O5 nanowires are not used, and the amount of potassium carbonate is increased accordingly. Specifically, it includes the following steps:

[0099] (1) Weigh the following substances in parts by mass: 62 parts quartz, 38 parts alumina powder, 0.7 parts polyvinyl alcohol (binder) with a degree of polymerization of 1000, and 14 parts potassium carbonate (sintering aid).

[0100] (2) Mix quartz and alumina powder and ball mill at 150 rpm for 7 hours. The grinding balls are zirconia balls of 5 mm, 8 mm and 10 mm in a mass ratio of 1:1:1. Then add binder and sintering aid and mix.

[0101] (3) Apply a directional pressure of 12 MPa to the mixture and press it to form a blank.

[0102] (4) The green blank is sintered in stages. The staged sintering procedure is as follows: 5 The temperature was increased from room temperature (25°C) to 600°C at a rate of ℃ / min, and held for 30 minutes. min; with 3 The temperature was increased from 600℃ to 1100℃ at a rate of ℃ / min and held for 30 minutes. min; with 2 The temperature was increased from 1100℃ to 1300℃ at a rate of ℃ / min and held for 2.5 seconds. h; then it is cooled in the furnace.

[0103] Comparative Example 2

[0104] This comparative example provides another method for preparing insulator ceramics, which is basically the same as the preparation steps in Example 1, except that potassium carbonate is not used, and other sintering aids without potassium are used instead. Specifically, it includes the following steps:

[0105] (1) Weigh the following substances in parts by mass: 62 parts quartz, 38 parts alumina powder (particle size D50 is 300 nm), 10 parts BaTi2O5 nanowires, 0.7 parts polyvinyl alcohol (binder) with a degree of polymerization of 1000, and 4 parts talc (sintering aid).

[0106] (2) Mix quartz, alumina powder and BaTi2O5 nanowires and ball mill them at 150 rpm for 7 hours. The grinding balls are zirconia balls of 5 mm, 8 mm and 10 mm in a mass ratio of 1:1:1. Then add binder and sintering aid and mix.

[0107] (3) Apply a directional pressure of 12 MPa to the mixture and press it to form a blank.

[0108] (4) The green blank is sintered in stages. The staged sintering procedure is as follows: 5 The temperature was increased from room temperature (25°C) to 600°C at a rate of ℃ / min, and held for 30 minutes. min; with 3 The temperature was increased from 600℃ to 1100℃ at a rate of ℃ / min and held for 30 minutes. min; with 2 The temperature was increased from 1100℃ to 1300℃ at a rate of ℃ / min and held for 2.5 seconds. h; then it is cooled in the furnace.

[0109] Comparative Example 3

[0110] This comparative example provides another method for preparing insulator ceramics, which is basically the same as the preparation steps in Example 1, except that: the first sintering aid is directly BaTi2O5 powder (particle size D50 is 300 nm), specifically including the following steps:

[0111] (1) Weigh the following substances in parts by mass: 62 parts of quartz, 38 parts of alumina powder (particle size D50 is 300 nm), 10 parts of BaTi2O5 powder (particle size D50 is 300 nm), 0.7 parts of polyvinyl alcohol (binder) with a degree of polymerization of 1000, and 4 parts of potassium carbonate (sintering aid).

[0112] (2) Mix quartz, alumina powder and BaTi2O5 powder, and ball mill at 150 rpm for 7 hours. The grinding balls are zirconia balls of 5 mm, 8 mm and 10 mm in a mass ratio of 1:1:1. Then add binder and sintering aid and mix.

[0113] (3) Apply a directional pressure of 12 MPa to the mixture and press it to form a blank.

[0114] (4) The green blank is sintered in stages. The staged sintering procedure is as follows: 5 The temperature was increased from room temperature (25°C) to 600°C at a rate of ℃ / min, and held for 30 minutes. min; with 3 The temperature was increased from 600℃ to 1100℃ at a rate of ℃ / min and held for 30 minutes. min; with 2 The temperature was increased from 1100℃ to 1300℃ at a rate of ℃ / min and held for 2.5 seconds. h; then it is cooled in the furnace.

[0115] Morphological characteristics:

[0116] The XRD patterns of the BaTi2O5 modified ceramics in Examples 1-4 and the insulator ceramics in Comparative Examples 1-3 are shown in the figure below. Figure 4 The results showed that the main phases of Examples 1-4 and the comparative examples were quartz phase and corundum phase.

[0117] A comparison of SEM images of the cross-sections of the BaTi2O5 modified ceramics of Examples 1-4 and the insulator ceramic of Comparative Example 1 is shown below. Figure 5 In the figure: (a) Example 1, (b) Example 2, (c) Example 3, (d) Example 4, (e) Comparative Example 1, (f) Comparative Example 2, (g) Comparative Example 3. The ceramic insulating parts of Examples 1 to 4, due to the addition of BaTi2O5 nanowires, can achieve more uniform pore distribution and more regular morphology while ensuring density. In particular, the number of pores in Example 1 is significantly reduced.

[0118] Performance testing:

[0119] The high-voltage insulator ceramics prepared in the Examples and Comparative Example 1 were subjected to the following tests:

[0120] (1) Ceramic density test

[0121] The density of ceramics was tested using Archimedes' displacement method. The ceramic sheet was baked at 105℃ for 30 minutes, cooled to room temperature, and its dry weight M0 was measured. Then it was placed in deionized water and its suspended mass M in the water was measured.

[0122] Density (g / cm³) 3 =M0 / (M0-M).

[0123] (2) Ceramic moisture absorption rate test

[0124] The ceramic sheet was baked at 105℃ for 30 minutes, cooled to room temperature and weighed for its dry weight M0. Then it was placed in deionized water, vacuumed to 0.1MPa, held for 10 minutes, slowly depressurized and continued to soak for 10 minutes. The surface water was wiped off and the wet weight M was weighed.

[0125] Moisture absorption rate (%) = (M-M0) / M0×100.

[0126] (3) Breakdown strength test

[0127] The breakdown strength test was conducted in accordance with the standard GB / T1408.1-2016 "Electrical strength test method for insulating materials - Part 1: Test at power frequency".

[0128] (4) Bending strength test

[0129] The breakdown strength test was conducted in accordance with the standard GB / T 8411.2-2008 "Ceramic and Glass Insulating Materials - Part 2: Test Methods".

[0130] The test results are shown in Table 1. Figure 6-7 .

[0131] Table 1 shows the performance test results of the ceramics in the examples and comparative examples.

[0132]

[0133] As shown in Table 1, comparing Examples 1-4 and the comparative examples, it can be seen that the ceramic insulating parts prepared in the embodiments of this application have a lower moisture absorption rate, and the breakdown strength and bending strength are effectively improved compared with traditional ceramic insulating parts.

[0134] Figure 5 The figure shows a comparison of the moisture absorption rate of the ceramic insulating components in the comparative example and Examples 1-4. As shown in the figure, the moisture absorption rates of Examples 1-4 are all lower than those of the comparative example, and the moisture absorption rate of Example 2 is reduced to below 0.5% as required by the national standard GB / T 8411.

[0135] Figure 6 The figure shows a comparison of the bending strength of the ceramic insulators in the comparative examples and Examples 1-4. As shown in the figure, the bending strength of Examples 1-4 is significantly improved.

[0136] The technical features of the above-described embodiments and examples can be combined in any suitable manner. For the sake of brevity, not all possible combinations of the technical features in the above-described embodiments and examples are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0137] The embodiments described above merely illustrate several implementation methods of this application and should not be construed as limiting the scope of the patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Furthermore, it should be understood that after reading the above teachings, those skilled in the art can make various alterations or modifications to this application, and the equivalent forms obtained also fall within the protection scope of this application. It should also be understood that technical solutions obtained by those skilled in the art based on the technical solutions provided in this application through logical analysis, reasoning, or limited experimentation are all within the protection scope of the appended claims. Therefore, the protection scope of this patent application should be determined by the appended claims, and the specification can be used to interpret the content of the claims.

Claims

1. A method for preparing BaTi2O5 modified ceramics, characterized in that, Includes the following steps: A mixed raw material is prepared by mixing insulator ceramic matrix raw material, BaTi2O5 nanowires, binder and sintering aid; After the mixed raw materials are pressed into green blanks, they are sintered in sections. The segmented sintering process includes: The temperature was increased from 20℃-40℃ to 550℃-650℃ at a rate of 4.5℃ / min-5℃ / min, and then held for 25min-35min. The temperature was increased from 550℃-650℃ to 1050℃-1150℃ at a rate of 2.5℃ / min-3.5℃ / min, and then held for 25min-35min. The temperature was increased from 1050℃-1150℃ to 1200℃-1300℃ at a rate of 1.5℃ / min-2.5℃ / min, and then held for 2-3 hours.

2. The preparation method according to claim 1, characterized in that, The BaTi2O5 nanowires have a length of 4μm-6μm; and / or, The diameter of the BaTi2O5 nanowires is 100nm-200nm.

3. The preparation method according to claim 2, characterized in that, The aspect ratio of the BaTi2O5 nanowires is 30:1-40:

1.

4. The preparation method according to any one of claims 1-3, characterized in that, The ceramic matrix raw material of the insulator includes the following oxides by mass percentage: SiO2 58.8%-63.7%, Al2O3 35.3%-40.2%, and unavoidable impurities ≤1%.

5. The preparation method according to any one of claims 1-3, characterized in that, The adhesive comprises at least one selected from polyvinyl alcohol, polyvinyl butyral, polyethylene glycol, methylcellulose, carboxymethylcellulose, paraffin wax, ammonium polyacrylate, and ethylene-vinyl acetate copolymer; and / or, The sintering aid includes one or more of the following: talc, potassium carbonate, magnesium oxide, calcium oxide, calcium carbonate, dolomite, feldspar, boric acid, zinc oxide, yttrium oxide, barium carbonate, and titanium dioxide.

6. The preparation method according to any one of claims 1-3, characterized in that, The mass of the BaTi2O5 nanowires accounts for 1%-7% of the total mass of the insulator ceramic matrix raw material; and / or, The binder accounts for 0.5%-0.8% of the total mass of the insulator ceramic matrix raw material; and / or, The mass of the sintering aid accounts for 3%-5% of the total mass of the insulator ceramic matrix raw materials.

7. The preparation method according to any one of claims 1-3, characterized in that, The step of pressing the mixed raw materials into a blank includes: subjecting the mixed raw materials to compression molding at 10MPa-15MPa.

8. BaTi2O5 modified ceramics, characterized in that, It is prepared by the preparation method described in any one of claims 1-7.

9. The BaTi2O5 modified ceramic according to claim 8, characterized in that, The BaTi2O5 modified ceramic has one or more of the following characteristics: (1) Moisture absorption rate ≤ 0.5%; (2) Breakdown strength ≥ 13kV / mm; (3) Bending strength ≥ 100 MPa.

10. The application of the BaTi2O5 modified ceramic as described in claim 8 or 9 in the preparation of high-voltage insulators.